2018
DOI: 10.7202/1052609ar
|View full text |Cite
|
Sign up to set email alerts
|

L’exploitation d’un corpus d’interactions en tandem anglais/français pour mieux comprendre les enjeux de la rétroaction corrective entre pairs

Abstract: Le tandem permet un apprentissage collaboratif où la relation entre les partenaires est moins hiérarchisée que dans les échanges entre professeur et élève en classe de langue. Chacun s’engage à faire progresser son partenaire dans sa langue et culture maternelles. Les apprentissages linguistiques et culturels y sont moins prévisibles, structurés et validés que dans le contexte institutionnel d’un cours. Les partenaires tandem accordent souvent plus d’importance à la fluidité et la convivialité de l’échange qu’… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…4 For a closer examination of the relationship between gaze and filled pauses, see Jehoul (2019) and Kosmala and Morgenstern (2017). 5 The exact proficiency levels of the students are not known, but their overall self-evaluated level is of 6.9/10 on average (Horgues and Scheuer, 2018). 6 Compare for example García-Amaya and Lang (2020) who conducted a crosslinguistic study on filled pauses based on Afrikaans-Spanish bilinguals, which is quite a rare population.…”
Section: Fundingmentioning
confidence: 99%
See 2 more Smart Citations
“…4 For a closer examination of the relationship between gaze and filled pauses, see Jehoul (2019) and Kosmala and Morgenstern (2017). 5 The exact proficiency levels of the students are not known, but their overall self-evaluated level is of 6.9/10 on average (Horgues and Scheuer, 2018). 6 Compare for example García-Amaya and Lang (2020) who conducted a crosslinguistic study on filled pauses based on Afrikaans-Spanish bilinguals, which is quite a rare population.…”
Section: Fundingmentioning
confidence: 99%
“…For a closer examination of the relationship between gaze and filled pauses, seeJehoul (2019) andKosmala & Morgenstern (2017).5 Kosmala's (in press) study on the same data also showed that non-native speakers did not only produce more complex sequences than native speakers, but also longer ones (combining a higher number of fluencemes) : from 1 to 14 markers in a sequence (M = 2.2) for learners, versus sequences of 1 to 8 (M = 1.8) for native speakers.6 The exact proficiency levels of the students are not known, but their overall selfevaluated level is of 6.9/10 on average(Horgues & Scheuer, 2018).…”
mentioning
confidence: 99%
See 1 more Smart Citation